Analysis of technical efficiency and its determinants among tobacco producers in Uganda: An application of data envelopment analysis (International Journal of Agricultural Research, Innovation and Technology, 2022)
This study aimed at analyzing technical efficiency and its determinants among tobacco producers in Uganda. To achieve this, primary data were drawn from 200 tobacco farmers using semi-structured questionnaires. In order to determine the technical efficiency and its determinants, Data envelopment analysis and Tobit regression model were used for the analysis respectively. From the results, we observed that the mean TE was 49%, implying that the farmers were 51% inefficient. Furthermore, input prices, land size, farmers’ age, farm income and farm location were found to be the determinants of technical efficiency. This study recommended that the government should subsidize farm inputs as well as training the farmers on input combinations in order to increase technical efficiency level.Int. J. Agril. Res. Innov. Tech. 12(1): 24-29, June 2022